Bank Interest Margins and Business Start-Up Collateral: Testing for Convexity - Burke, Andrew; Hanley, Aoife (Blackwell Publishing, 2006)
The paper investigates the relationship between bank interest rate margins and collateral for loans issued to new ventures. The analysis finds a convex U-shaped relationship. The results indicate that while provision of collateral initially reduces bank exposure to risk (through security, more optimal levels of capital and lower moral hazard among entrepreneurs) that beyond a point its association with higher wealth gives rise to greater risk taking propensity among entrepreneurs and ultimately higher interest rates. This indicates that banks’ pricing policy may even help level the competitive playing field somewhat between ventures launched by higher and moderately lower wealth entrepreneurs.
Keywords: asymmetric information; Bank Lending; Credit; Credit Constraints